Disaster Education through Participatory Mapping in Abrasion Prone Areas in Sarang, Central Java - Nur Hamid; Rina Purwaningsih; Juhadi Juhadi; Elvara Norma Aroyandin; Helmi Suyanto (Universitas Gadjah Mada, 2022)
One of the abrasion mitigations is mapping vulnerable areas through participatory mapping. Compared to conventional mapping, participatory mapping is considered more effective because, through this mapping, complete and detailed information will be obtained relatively quickly. However, given the limitations of the community, the participatory mapping process must be carried out through empowerment. Participatory mapping is one part of disaster education for the community. This research will provide disaster education through socialization and training on participatory mapping of GIS-based abrasion-prone areas in Sarang District, Rembang Regency based on community empowerment through a mixed-methods approach. The techniques used in data collection are interview, observation, questionnaire, a document study, and FGD techniques. The results show that this research has carried out participatory mapping based on community empowerment through preparation, implementation, evaluation, and monitoring stages. The results of participatory mapping are the active involvement of the community physically and mentally, the formation of a map of the occurrence of abrasion, and increasing the capacity of knowledge, attitudes, and perceptions of the community. The resulting maps can be used as recommendations to local governments and guidelines for local communities.